Bottom‐Up Synthesized Nanoporous Graphene Transistors. (21st August 2021) - Mutlu, Zafer; Jacobse, Peter H.; McCurdy, Ryan D.; Llinas, Juan P.; Lin, Yuxuan; Veber, Gregory C.; Fischer, Felix R.; Crommie, Michael F.; Bokor, Jeffrey
Abstract: Nanoporous graphene (NPG) can exhibit a uniform electronic band gap and rationally‐engineered emergent electronic properties, promising for electronic devices such as field‐effect transistors (FETs), when synthesized with atomic precision. Bottom‐up, on‐surface synthetic approaches developed for graphene nanoribbons (GNRs) now provide the necessary atomic precision in NPG formation to access these desirable properties. However, the potential of bottom‐up synthesized NPG for electronic devices has remained largely unexplored to date. Here, FETs based on bottom‐up synthesized chevron‐type NPG (C‐NPG), consisting of ordered arrays of nanopores defined by laterally connected chevron GNRs, are demonstrated. C‐NPG FETs show excellent switching performance with on–off ratios exceeding 10 4, which are tightly linked to the structural quality of C‐NPG. The devices operate as p‐type transistors in the air, while n‐type transport is observed when measured under vacuum, which is associated with reversible adsorption of gases or moisture. Theoretical analysis of charge transport in C‐NPG is also performed through electronic structure and transport calculations, which reveal strong conductance anisotropy effects in C‐NPG. The present study provides important insights into the design of high‐performance graphene‐based electronic devices where ballistic conductance and conduction anisotropy are achieved, which could be used in logic applications, and ultra‐sensitive sensors for chemical or biological detection. Abstract : The charge‐transport properties of bottom‐up synthesized nanoporous graphene are investigated both experimentally and theoretically. The results provide important insights into the design of high‐performance graphene‐based electronic devices.